2001
DOI: 10.1111/j.1751-8369.2001.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene palaeoceanography in Van Mijenfjorden, Svalbard

Abstract: Based on detailed stratigraphical analysis of sediment cores spanning the last ca. 4000 calendar years, we reconstruct the palaeoceanograhic changes in the fiord Van Mijenfjorden, western Svalbard. Benthic foraminiferal δ18O indicate a gradual reduction in bottom water salinities between 2200 BC and 500 BC. This reduction was probably mainly a function of reduced inflow of oceanic water to the fiord, due to isostatic shallowing of the outer fiord sill. Stable salinity conditions prevailed between 500 BC and. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Previously it has been suggested that many of the Svalbard glaciers reached their postglacial maxima in the late Holocene, most notably at the end of the LIA (Salvigsen et al 1992;Svendsen & Mangerud 1997;Sletten et al 2001;Humlum et al 2005). However, several Svalbard glaciers are suggested to have experienced pre-LIA advances (Salvigsen et al 1990;Ronnert & Landvik 1993;Werner 1993;Andersson et al 2000;Hald et al 2001;Lønne 2005;Kempf et al 2013;Reusche et al 2014). The data from Mohnbukta support these findings and indicate that a glacial advance, more extensive than the LIA advance, has also taken place on the east coast of Spitsbergen.…”
Section: A Possible Early Holocene Glacier Advance In Mohnbuktamentioning
confidence: 81%
See 3 more Smart Citations
“…Previously it has been suggested that many of the Svalbard glaciers reached their postglacial maxima in the late Holocene, most notably at the end of the LIA (Salvigsen et al 1992;Svendsen & Mangerud 1997;Sletten et al 2001;Humlum et al 2005). However, several Svalbard glaciers are suggested to have experienced pre-LIA advances (Salvigsen et al 1990;Ronnert & Landvik 1993;Werner 1993;Andersson et al 2000;Hald et al 2001;Lønne 2005;Kempf et al 2013;Reusche et al 2014). The data from Mohnbukta support these findings and indicate that a glacial advance, more extensive than the LIA advance, has also taken place on the east coast of Spitsbergen.…”
Section: A Possible Early Holocene Glacier Advance In Mohnbuktamentioning
confidence: 81%
“…A few Svalbard glaciers, mainly on the west coast of Spitsbergen, have been suggested to experience surgetype advances prior to the historical period, based on dates from marine sediment cores and terrestrial glacial deposits (Punning et al 1976;Hald et al 2001;Kempf et al 2013). Nathorstbreen in Van Keulenfjorden experienced a surge-type advance between 2790-2610 cal.…”
Section: Glaciological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Several marine sedimentary records span the Holocene history of the area (Elverhi et al 1995;Hald et al 2001Hald et al , 2004Hald et al , 2007Slubowska et al 2005;Forwick & Vorren 2007;Rasmussen et al 2007; Slubowska-Woldengen et al 2007). Their resolution for the last millennium is relatively low, but some records have revealed abrupt environmental shifts (e.g.…”
mentioning
confidence: 99%